Characteristics and optimization of core local network: Big data analysis of football matches. (September 2020) - Wu, Yao; Xia, Zeyu; Wu, Tian; Yi, Qing; Yu, Runyu; Wang, Jun
Abstract: The current study constructed social network using player positions and passing process based on available literature. Multiple indicators were used to measure the importance of positions comprehensively. The results showed that in the football passing process, the attacking midfielder was the most important position, followed by the central defending midfielder. Based on two-sample difference tests, the results showed that the winning teams usually had better performance on positions of forward on left, central forward, defender on left and defender on right. To analyze the effects of playing positions on the whole network and test the sensitivity of passing networks, we deleted n ( n = 1, 2, 3…, 10) positions of a team, and then tested the efficiency of the networks based on positions left.